2003
DOI: 10.1063/1.1541114
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoretic assembly of oriented and switchable two-dimensional photonic crystals

Abstract: We show that one-and two-dimensional crystals can be assembled from suspensions of latex or silica microspheres subjected to an alternating electric field in a gap between planar electrodes on a surface. These crystals, with areas above 25 mm 2 , are specifically oriented without the need for micropatterned templates. The order-disorder transitions take place within seconds and can be repeated tens of times by switching the field on and off. The particles accumulate on the surface between the electrodes due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(131 citation statements)
references
References 17 publications
1
129
0
1
Order By: Relevance
“…[65] The approach was also extended to planar monolayers crystallized by alternating electric fields at the electrodes [66] and in a field gradient between two electrodes. [67] It was found that the application of alternating electric fields produced monolayers with a higher degree of long range Theory 27 order compared to constant electric field as nucleation rates can be controlled more precisely with alternating fields. [66] …”
Section: Electrophoretic Depositionmentioning
confidence: 99%
“…[65] The approach was also extended to planar monolayers crystallized by alternating electric fields at the electrodes [66] and in a field gradient between two electrodes. [67] It was found that the application of alternating electric fields produced monolayers with a higher degree of long range Theory 27 order compared to constant electric field as nucleation rates can be controlled more precisely with alternating fields. [66] …”
Section: Electrophoretic Depositionmentioning
confidence: 99%
“…In the presence of a large number of particles [1,6], particles interact with the external electric field as well as each other when they are close enough. Usually, mutual interactions among particles result in an aggregated chain when the particle concentration is diluted [35][36][37][38]. In the case of dense particles, these dipolar chains combine to form complex two-or threedimensional structures [39].…”
Section: Particle Assemblymentioning
confidence: 99%
“…1F). [40] The forces involved include induced dipole chaining and dielectrophoresis, the mobility of particles along the direction of the gradient of the field. [26] The application of AC fields can also lead to lateral motion of anisotropic particles due to induced-charge electrophoresis.…”
Section: Progress Reportmentioning
confidence: 99%